Best practices for teaching statistics and research methods in the behavioral sciences - Dunn, Dana S.; Smith, Randolph A.; Beins, Bernard (Lawrence Erlbaum Associates, 2007)
Provides a showcase for "best practices" in teaching the critical core courses in two- and four-year colleges and in universities. This book covers a variety of topics germane to teaching these courses including ways to integrate them, how to promote ethical conduct, and how to create writing intensive programs.